To find the 9th term of the arithmetic sequence using the explicit formula \( A_n = 14 + (n - 1) \cdot 12 \), you need to substitute \( n = 9 \) into the formula.
Starting with the formula:
\[ A_n = 14 + (n - 1) \cdot 12 \]
Substituting \( n = 9 \):
\[ A_9 = 14 + (9 - 1) \cdot 12 \]
Now calculate \( (9 - 1) \):
\[ A_9 = 14 + 8 \cdot 12 \]
Now, calculate \( 8 \cdot 12 \):
\[ A_9 = 14 + 96 \]
Finally, add 14 and 96:
\[ A_9 = 110 \]
So the 9th term of the sequence is \( 110 \).
However, it looks like \( 110 \) isn't one of the provided answers. Please double-check the options or the formula in case there's any misunderstanding or typographical error.